THE IMPLEMENTATION OF MARRIAGE GUIDANCE FOR PROSPECTIVE BRIDALS BY THE RELIGION MINISTRY OF MANADO - Salma Salma; Ahmad Rajafi (IAIN Manado, 2020)
Divorce in Manado includes the highest in North Sulawesi, while the office of Religious Affairs has long run the course for prospective brides. After that, it brought forth a new regulation on marriage guidance brides was born in 2009 with a detailed curriculum and modules in 2016. This marriage guidance is the urgency of this research to examine the implementation of marriage guidance in Manado's city. This research's field is qualitative with data collection through observation, interviews, documentation, and the SWOT analysis approach. The results were found that many obstacles in the level of implementation, from disproportionate budgeting, not using a certified facilitator, the implementation that was not in accordance with the technical guidelines namely for sixteen hours of learning divided into two days; with a division of time of eight hours on the first day and eight hours on the second day.